Owls and Larks in Mice - Pfeffer, Martina; Wicht, Helmut; von Gall, Charlotte; Korf, Horst-Werner (Frontiers in Neurology, 2015)
Humans come in different chronotypes and, particularly, the late chronotype (the so-called owl) has been shown to be associated with a number of health risks. Recent studies indicate that laboratory mice also display various chronotypes. In mice as well as in humans, the chronotype shows correlations with the period length and rhythm stability. In addition, some mouse models for human diseases show alterations in their chronotypic behavior which are comparable to those humans. Thus, analysis of the behavior of mice is a powerful tool to unravel the molecular and genetic background of the chronotype and the prevalence of risks and diseases that are associated with it. In this review, we summarize the correlation of chronotype with free-running period length and rhythm stability in the most commonly used inbred mouse strains, in mice with a compromised molecular clockwork and in a mouse model for neurodegeneration.